Integration of ATAC-seq and RNA-seq reveals signal regulation during post-molt and inter-molt stages in muscle of Eriocheir sinensis - Wang, Bin; Li, Jingjing; Zhang, Mingzhi; Li, Anqi; Song, Zhentao; He, Zhen; Zhang, Ruiqi; Hao, Tong; Sun, Jinsheng (Frontiers in Marine Science, 2025)
IntroductionThe molting processes are crucial for the survival and development of crustaceans. Eriocheir sinensis demonstrates representative discontinuous growth during molting, while muscle is the most obvious tissue exhibiting this property. However, the signal regulation mechanisms involved in muscle during molting remain unexplored.MethodsIn this work, a comprehensive analysis of the gene expressions in E. sinensis muscle between post-molt and inter-molt stages were performed by integrating the ATAC-seq and RNA-seq techniques.ResultsThe integration analysis identified 446 up-regulated and 21 down-regulated genes in the two stages. GO enrichment analysis revealed that the up-regulated genes are largely associated with protein phosphorylation and phosphorus metabolism, while the down-regulated genes are mainly involved in DNA metabolism, transcription, cell adhesion, and G protein-coupled receptor (GPCR) signaling pathway. In all the enriched signaling pathways, GPCR signaling pathway includes the most differentially expressed genes (8 genes), which underlines its importance in the signal transduction from the post-molt stage to the inter-molt stage. Further protein structure analysis and RT-qPCR validation confirmed five GPCR genes related to molting process, in which four genes (GRM7, FMRFaR, mth2, gpr161) are active during the post-molt stage and one gene (moody) functions during the inter-molt stage.DiscussionThese findings highlight the key regulatory proteins and pathways involved in E. sinensis muscle during molting and also offer foundational data for studying the mechanisms of molting and discontinuous growth in crustaceans.